Enhancing Local Economic Growth through Digital Cooperative-Based MSME Development in Support of the Village SDGs Program - Prihandono, Dorojatun; Airyq, Irnin Miladdyan; Wijaya , Angga Pandu; Witiastuti, Rini Setyo; Putri, Vini Wiratno (Indonesian Journal of Devotion and Empowerment, 2025)
MSMEs are an integral part of advancing the rural economy and realizing the SDGs at the grassroots/village level. Many rural MSMEs often seem not to feel the full impact of this potential, as they are hindered by a lack of digital literacy, limited application of marketing strategies, and only weak ties to the economy. The primary objective of this program is to enhance the economic potential of MSMEs in Kalisidi Village, West Ungaran District, Semarang Regency, by utilizing an online cooperative application. A total of 30 MSMEs in Kalisidi Village participated in a community service program that included explanations and group coaching. Some of these activities included community training, presentations, and simulated use of a digital platform for a cooperative. The findings indicated that the trainees developed a deeper understanding of digital marketing and had high confidence in leveraging technology to conduct business. The digital platform also established an integrated business environment for MSMEs, facilitating collaboration in branding, shared resource deployment, and new market entry. This initiative demonstrates that implementing a digital cooperative model can effectively catalyze inclusive and sustainable economic development in rural areas. Furthermore, it contributes to the achievement of several SDG targets, particularly SDG 8 (decent work and economic growth) and SDG 811 (sustainable cities and communities). Digital integration rooted in local potential is key to building a resilient and independent village economy.